A new syndrome of autosomal recessive nephropathy, deafness, and hyperparathyroidism. Issue 5 (May 1989) - Edwards, B D; Patton, M A; Dilly, S A; Eastwood, J B
Abstract : A consanguineous Pakistani family is described in which family members developed renal failure without haematuria, parathyroid hyperplasia, and sensorineural deafness. We believe the condition to be inherited as an autosomal recessive and to be distinct from Alport's syndrome, which is an X linked condition usually associated with haematuria.